Utilization of Soapberry as a Natural Surfactant in Cashew Nut Shell Liquid Bioinsecticide Formulation in Soybean Pest Management - Astriani, Dian; Mildaryani, Warmanti; Solichah, Ummu (KnE Life Sciences, 2022)
The demand for soybean has been steadily increasing year after year. Pests are one of the most significant barriers to increasing soybean production. The goal of this study was to determine what concentration of soapberry fruit extract to use as an adjunctive ingredient in cashew nut shell liquid (CNSL) formulations to obtain the best pest control effect and soybean growth and yield. This study used a randomized complete block design with a single factor: soapberry extract concentration. The research included four treatments: application of CNSL formulations containing 4%, 3%, 2%, and 0% soapberry extract, application of CNSL formulations containing 1 g/liter detergent, synthetic pesticides (Fastac 1-2 liters/ha), and no pesticides as a control. Insecticide applications were effective against grasshopper and pod-sucking bugs in soybean cultivation; the CNSL with 3%, 4% soapberry and the CNSL with detergent had effectiveness comparable to the synthetic insecticides. Soybean growth was unaffected by any of the CNSL formulations or synthetic insecticide applications. However, using a CNSL formulation with 4% soapberry increased soybean yield as much as using a synthetic insecticide; it did not differ significantly from using a CNSL formulation with detergent. The soybean yield was highest in the CNSL formulation with detergent. Keywords: Keywords: soybean, soapberry, CNSL, pest